Contested Landscape and Spirit of Place: The Case of the Olive Trees and an Urban Neighborhood in Israel - Amit-Cohen, Irit (Journal for Geography, 2009)
Cultural heritage and cultural landscape are a set of human products reflecting the needs, thoughts and memories of society. They represent and symbolize relationships of power and control, from which they emerged, and the human processes that transformed and continue to transform them. Such transformations create new cultural landscapes and cultural heritage that often conceal the processes – political, social, cultural, ideological and economic, that have created them. The purpose of this paper is to analyze a contested geographical environment, where two cultures, the Jewish Zionist culture and the Arab Moslem culture, compete over the land and its cultural heritage, and therefore each of them, has its own interpretations. The aim is to define the landscape, its spirit and its representation, which emerge from these competitions and disputes; characterize it and analyze its symbols and its uses, primarily for the purpose of forming and constructing identities.
Keywords: Contested Landscape; Cultural Landscape; Icon; Symbol